Back to gold: Sterling in 1925 - Stefan Gerlach; Peter Kugler (Goethe University Frankfurt, Center for Financial Studies (CFS), 2015)
Expectations of Sterling returning to Gold have been disregarded in empirical work on the US dollar - Sterling exchange rate in the early 1920s. We incorporate such considerations in a PPP model of the exchange rate, letting the probability of a return to gold follow a logistic function. We draw several conclusions: (i) the PPP model works well from spring 1919 to spring 1925; (ii) wholesale prices outperform consumer prices; (iii) allowing for a return to gold leads to a higher speed of adjustment of the exchange rate to PPP; (iv) interest rate differentials and the relative monetary base are crucial determinants of the expected return to gold; (v) the probability of a return to Gold peaked at about 72% in late 1924 and but fell to about 60% in early 1925; and (vi) our preferred model does not support the Keynes' view that Sterling was overvalued after the return to gold.
urn:nbn:de:hebis:30:3-382852
Keywords: E5; F31; N1; 330; Gold Standard; Sterling; exchange rate; PPP; expectations